2020
DOI: 10.1371/journal.pone.0231301
|View full text |Cite
|
Sign up to set email alerts
|

Do railway lines affect the distribution of woodland birds during autumn?

Abstract: Research results on the impact of railway noise on birds show a variety of bird responses. These behaviours are often different from those exhibited by birds occupying habitats along tarred roads. Knowledge of this subject is still incomplete. We attempted to define the influence of a heavily transited railway line on bird communities at stopover sites near the tracks during the autumn migration period. Birds were counted using the point method at 45 observation points located at three distances (30 m, 280 m, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
(80 reference statements)
0
9
1
Order By: Relevance
“…Though the noise from busy roadside traffic provides negative impact on many bird species (Rheindt 2003, Summers et al 2011, in our study, we did not observe any negative interactions with the train movements to their surroundings. Such bird species frequently observed in station areas did not react much in response to the noise made by the movement of trains through the station (Wiącek et al 2015(Wiącek et al , 2019(Wiącek et al , 2020. In the present observations, the railway stations across urban-rural gradient appear to bear a positive impact on the bird species assemblages.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Though the noise from busy roadside traffic provides negative impact on many bird species (Rheindt 2003, Summers et al 2011, in our study, we did not observe any negative interactions with the train movements to their surroundings. Such bird species frequently observed in station areas did not react much in response to the noise made by the movement of trains through the station (Wiącek et al 2015(Wiącek et al , 2019(Wiącek et al , 2020. In the present observations, the railway stations across urban-rural gradient appear to bear a positive impact on the bird species assemblages.…”
Section: Discussioncontrasting
confidence: 48%
“…In this study, we found relatively higher abundance of omnivores in each selected railway stations irrespective of the urban-rural gradient followed by insectivores, while the abundance of other four guilds were the least. In the railway tracks near the forest areas, the insectivores dominate owing to the abundance of the macroinvertebrates like insects, more likely due to the edge effect (Wiącek et al 2020). The granivorous bird species were the most abundant in rural railway stations as compared to urban and suburban station regions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Species migrating, flying past or not being associated with these habitats were ignored. The observer was highly experienced in bird censusing and used the same counting method as in studies on other habitats (Wiącek et al 2015a(Wiącek et al , 2015b(Wiącek et al , 2019(Wiącek et al , 2020. Birds were with great care, while moving slowly from one point to the next so as not to record the same birds twice at consecutive points.…”
Section: Methodsmentioning
confidence: 99%
“…A straightforward way of assessing the effect of traffic noise on birds is to study the changes in breeding density near a busy road. It has long been known that the numbers and species diversity of birds decrease in the vicinity of roads (reiJnen et al 1995(reiJnen et al , 1996, although some birds, in line with the edge effect, may occur in larger densities close to transport routes (kuitunen et al 2003;Benitez loPez et al 2010), particularly along railway lines (Wiącek et al 2015a(Wiącek et al , 2019(Wiącek et al , 2020.…”
Section: Introductionmentioning
confidence: 99%